The Influence of the National Political Scene on the Behavior of Local Politicians and Voters in Polish Local Elections in 2018 - Kozierska, Joanna (Political Preferences, 2019)
Polish local elections in 2018, many months before their commencement, became one of the main elements of the political discourse. Due to the specificity of the electoral calendar, for the first time since the parliamentary and presidential elections in 2015, voters had to assess the actions taken by the Law and Justice (Prawo i Sprawiedliwość, PiS) in the electoral act. Of course, this could only happen indirectly, precisely through local elections, which due to their specificity, are not able to fully reflect the balance of powers that operates on the national arena. However, also in this way voters could refer to national events. Expressing support for them by voting on PiS, or by showing negations of their actions by voting for groups remaining in opposition. The aim of the paper is to check whether, in the perception of voters, events on the national political arena determine the behavior of two types of participants in local elections: local politicians and voters.